Penggunaan model pembelajaran course review horay (crh) untuk meningkatkan penguasaan konsep perjuangan mempertahankan kemerdekaan indonesia pada siswa kelas V sekolah dasar - Maria Christy Puspitasari; Hadiyah Hadiyah; Chumdari Chumdari (Universitas Sebelas Maret, 2019)
The purporse of this research is to improve concept mastery of Indonesia independent struggle by using CRH model for 5th grade students of SD N Bulakrejo 02 Sukoharjo on 2018/2019. This research is a Classroom Action Research (CAR). This study was conducted in 2 cycles with each cycle consisting of planning, implementing actions, observing, and reflecting. This research uses content validity, technique triangulation, and source triangulation. The results of this study prove that the average pretest score is 58,69 with classical completeness of 12,5%. In the first cycle the average value increased to 72,87 with classical completeness of 43,75%. In the second cycle there was an increase to 84,18 with 87,5% classical completeness. The conclusion of this study is that by CRH learning model, it can improve the concept mastery of Indonesia independent struggle in 5th grade students of SD N Bulakrejo 02 Sukoharjo on 2018/2019.